Porównanie postaw przedsiębiorczych studentów studiów ekonomicznych, społecznych i humanistycznych - Dąbrowska, Karolina; Skowron, Mariusz (Annales. Etyka w Życiu Gospodarczym, 2015)
Success in economic life is a result of the interaction of many factors, which indifferent ways are developed from the individual characteristics of the person, a specificway of thinking and the ability to perceive oneself in the future. At the sametime, more and more attention is focused on the influence of the entrepreneurialcharacteristics of individuals on their career development and career building process.The impact of personal experience on the perception of individual chances onthe labour market is also emphasized. The purpose of this paper is, therefore, toidentify the differences in enterprising attitudes of students of the humanities andstudents of economics, as well as compare the characteristics of entrepreneurialabilities between both student groups on the basis of empirical research conductedamong students at the University of Lodz.